SOMATISMS IN THE SPANISH LANGUAGE: LINGUOCULTURAL AND SEMANTIC FEATURES - Djalilova , Sarvaroy (Scientific practical conference, 2025)
This article explores the semantic, cultural, and cognitive features of somatisms in the Spanish language, emphasizing their central role in expressing emotions, social relationships, and culturally embedded values. Somatic lexemes such as cabeza, cara, ojo, mano, and corazón function not only as designations of body parts but also as carriers of symbolic meanings that reflect the Spanish worldview. The study demonstrates that Spanish somatisms form a highly productive idiomatic system shaped by conceptual metaphors, emotional expressiveness, and historical-cultural traditions, including the influence of Catholic symbolism. Through an analysis of somatic idioms, the article highlights core cultural codes such as honor, sincerity, emotional openness, and social cohesion. The findings show that somatisms play an essential role in structuring Spanish linguistic identity and represent a key element for understanding the cultural and communicative practices of the Spanish-speaking world.